Exploring the Challenges and Opportunities of Religious Moderation Policies in Islamic Education - Zurayah, Helva; Lubis, Putri Handayani (Al-Hayat: Journal of Islamic Education, 2026)
This study aims to explore the challenges and opportunities in the implementation of religious moderation policies in Pontianak, Indonesia, in relation to the achievement of the Sustainable Development Goals (SDGs), particularly SDG 4, SDG 5, and SDG 10. This research is important for understanding the contribution of religious moderation in fostering an inclusive and peaceful society. A qualitative approach was employed through a case study in Pontianak, using in-depth interviews and field observations. Data were collected from religious figures, community leaders, and members of society from various religious and ethnic backgrounds, and were analysed thematically. The findings indicate that the main challenges include the politicisation of policies and conservative groups that view religious moderation merely as passive tolerance. Opportunities are driven by high acceptance among youth and academics, which strengthens social capital. A significant impact is found in the field of education, where initiatives for integrating religious moderation have reinforced tolerance and inclusivity. Public acceptance varies, showing critical interpretational gaps. This study is limited to Pontianak and may not fully represent the situation across Indonesia. The limitations of data and observation time also affected the depth of analysis. This research provides an important contribution to the development of more inclusive and contextual religious moderation policies in Indonesia, with opportunities for further research in other regions with different social conditions.